2017
DOI: 10.1038/s41598-017-14037-0
|View full text |Cite
|
Sign up to set email alerts
|

Photosensing and Thermosensing by Phytochrome B Require Both Proximal and Distal Allosteric Features within the Dimeric Photoreceptor

Abstract: Phytochromes (Phys) encompass a diverse collection of bilin-containing photoreceptors that help plants and microorganisms perceive light through photointerconversion between red light (Pr) and far-red light (Pfr)-absorbing states. In addition, Pfr reverts thermally back to Pr via a highly enthalpic process that enables temperature sensation in plants and possibly other organisms. Through domain analysis of the Arabidopsis PhyB isoform assembled recombinantly, coupled with measurements of solution size, photoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
43
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 63 publications
(136 reference statements)
12
43
1
2
Order By: Relevance
“…Detailed protocols for plant growth conditions and plasmid constructs, in vitro phyB thermal reversion assay (37), hypocotyl elongation assay and statistical analysis, fixation of seedlings and confocal microscopy, protein extraction and Western blot experiments, in vitro co-IP/binding assay and yeast two-hybrid analysis, and LUC-based circadian clock assays are described in SI Appendix, Materials and Methods. All primers used for cloning are listed in SI Appendix, Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed protocols for plant growth conditions and plasmid constructs, in vitro phyB thermal reversion assay (37), hypocotyl elongation assay and statistical analysis, fixation of seedlings and confocal microscopy, protein extraction and Western blot experiments, in vitro co-IP/binding assay and yeast two-hybrid analysis, and LUC-based circadian clock assays are described in SI Appendix, Materials and Methods. All primers used for cloning are listed in SI Appendix, Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Removal of the NTE from the phyB protein accelerated thermal reversion of phyB PSM fragments in vitro and abolished phyB localization to PBs in Arabidopsis (Chen et al, 2005;Burgie et al, 2014;Burgie et al, 2017). In general, the NTE of phyB is assumed to be important for thermal stability of the Pfr form.…”
Section: Researchmentioning
confidence: 99%
“…In an Arabidopsis thaliana PhyB truncation study, PhyB (1-450 aa) failed to associate with PIF6 reversibly (22). A recent study demonstrated that PhyB (1-450 aa) truncation has an absorption maximum at 693 nm (Pfr) when PCB was used as a chromophore, although full-length PhyB shows maximum absorption at 714 nm (Pfr) (17). The reversible control of the truncated PhyB-PIF6 association we demonstrated might be Figure 2.…”
Section: Discussionmentioning
confidence: 81%
“…In an Arabidopsis thaliana PhyB truncation study, PhyB (1–450 aa) failed to associate with PIF6 reversibly . A recent study demonstrated that PhyB (1–450 aa) truncation has an absorption maximum at 693 nm (Pfr) when PCB was used as a chromophore, although full‐length PhyB shows maximum absorption at 714 nm (Pfr) . The reversible control of the truncated PhyB‐PIF6 association we demonstrated might be attributable to the difference of irradiation conditions: we irradiated with 735 nm light for the dissociation of PhyB‐PIF6 binding, whereas photoirradiation with light that was >750 nm was applied using a near‐IR glass filter in an earlier study .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation